2007
DOI: 10.1080/00268970701651714
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on the intramolecular spin exchange in biradicals at room temperature

Abstract: Solvent effects on intramolecular electron spin exchange in biradicals have been investigated in various solvents by electron spin resonance (ESR) spectroscopy at room temperature. Biradicals containing different radical fragments and bridges of different length and composition have been used. Interactions between solvent molecules and biradicals were found to take place at the radical fragment as well as at the functional group in the connecting bridge and have been proved to have an influence on the intramol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…Owing to the presence of two unpaired electrons in the dinitroxide radicals, EPR spectroscopy is an outstanding tool for the characterization of the intramolecular electron spin exchange and conformational dynamics . Analysis of a dinitroxide EPR spectrum can provide valuable information on intramolecular movements, thermodynamics, and spin exchange mechanism …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the presence of two unpaired electrons in the dinitroxide radicals, EPR spectroscopy is an outstanding tool for the characterization of the intramolecular electron spin exchange and conformational dynamics . Analysis of a dinitroxide EPR spectrum can provide valuable information on intramolecular movements, thermodynamics, and spin exchange mechanism …”
Section: Resultsmentioning
confidence: 99%
“…In the case of tri‐ and tetranitroxide radicals, three ( J 12 , J 13 , J 23 ) or six ( J 12 , J 13 , J 14 , J 23 , J 24 , J 34 ) exchange couplings, respectively, define the spin exchange . The structure of the nitroxide fragments, along with the type of connecting bridge, has a substantial effect not only on the J value, but also on the mechanism of the spin exchange …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Areas in RTILs (polar, non-polar), in which spin probes (hydrophilic, charged, hydrophobic) are localized were determined. Just recently, attention of the scientists was attracted to another type of molecular motions in the ionic liquids (Tran et al, 2007a(Tran et al, , 2009. Such processes as well as solvent effects on them can be examined in detail by EPR spectroscopy with the use of stable nitroxide biradicals (Parmon et al, 1977a(Parmon et al, , 1980.…”
mentioning
confidence: 99%
“…Such processes as well as solvent effects on them can be examined in detail by EPR spectroscopy with the use of stable nitroxide biradicals (Parmon et al, 1977a(Parmon et al, , 1980. Solvent effects on intramolecular electron spin exchange in biradicals have been investigated in various solvents, including Bmim + PF 6 -, by electron spin resonance (ESR) spectroscopy at room temperature (Tran et al, 2007a). Using biradicals contained different radical fragments and bridges of various length and composition, it was demonstrated that interactions among solvent molecules and biradicals took place at the radical fragment and also at the functional group in the connecting bridge.…”
mentioning
confidence: 99%